Resveratrol: Potential Application in Sepsis - Li, Jiajia; Zeng, Xiaoting; Yang, Fuxun; Wang, Lan; Luo, Xiaoxiu; Liu, Rongan; Zeng, Fan; Lu, Sen; Huang, Xiaobo; Lei, Yu; Lan, Yunping (Frontiers in Pharmacology, 2022)
Sepsis is a life-threatening organ dysfunction syndrome caused by host response disorders due to infection or infectious factors and is a common complication of patients with clinical trauma, burns, and infection. Resveratrol is a natural polyphenol compound that is a SIRT-1 activator with anti-inflammatory, antiviral, bacterial, fungal inhibition, and cardiovascular and anti-tumor protective effects. In recent years, some scholars have applied resveratrol in animal models of sepsis and found that it has organ protective effect and can improve the survival time and reduce the mortality of animals with sepsis. In this study, Medline (Pubmed), Embase, and other databases were searched to retrieve literatures published in 2021 using the keyword "resveratrol" and "sepsis" and then the potential of resveratrol for the treatment of sepsis was reviewed and prospected to provide some basis for future clinical research.